DERADICALIZATION AT STATE ISLAMIC RELIGIOUS UNIVERSITIES IN EAST JAVA, INDONESIA - Muwahid, Muwahid; Syihabudin, Athok; Lailatul, Nur Lailatul Musyafa’ah (IAI Darussalam, 2023)
Deradicalization is important to do in an effort to prevent the academic community from being exposed to radical ideas. Several universities carry out deradicalization policies to prevent the spread of radical understanding in Islamic universities in East Java, Indonesia, such as UIN Sunan Ampel Surabaya (UINSA) and UIN Sayyid Ali Rahmatullah Tulungagung (UIN SATU). This study aims to answer two problems: First, how is the deradicalization policy applied at UINSA and UIN SATU; second, how effective is the deradicalization policy at UINSA and UIN SATU. This research is field research with a case approach. The case approach analyzes the role model of deradicalization at UINSA and UIN SATU. The research concluded that the deradicalization policy implemented at UINSA through various forms, including Ma'had activities, regulations on Student and Lecturer Code of Ethics, studies, and seminars on anti-radicalism and terrorism, integration of teaching in Pancasila and Citizenship courses, philosophical Integrated Twin Tower, Nusantara Studies with INNUS (Institute for Nusantara Studies), and the mainstreaming of moderate Islamic understanding. The deradicalization policy applied at UIN SATU uses six models: organizing seminars, studies with the theme of deradicalization, managing ma’had diniyah, Student Code of Ethics, supporting all religious moderation activities, optimizing local wisdom, and creating a learning environment that supports deradicalization programs. The deradicalization program within the scope of UINSA and UIN SATU effectively prevents radicalism on campus.